The emerging role of exosomal LncRNAs in chronic fatigue syndrome: from intercellular communication to disease biomarkers - Wang, Lei; Xu, Yujia; Zhong, Xiang; Wang, Guiping; Shi, Zijun; Mei, Can; Chen, Linwanyue; Zhan, Jianbo; Cheng, Jing (Frontiers in Molecular Biosciences, 2025)
Chronic fatigue syndrome (CFS) is a complex disease involving multiple systems throughout the body with unknown pathogenesis and is characterized by chronic fatigue. To date, no effective treatment for CFS has been found, as well as biomarkers for early identification of diagnosis. However, exosomes, a subpopulation of extracellular vesicles (EVs), are membranous vesicles secreted by cells into the surrounding environment, and long noncoding RNAs (LncRNAs) in EVs can mediate inter-organ and inter-cellular communication, which maybe associate with CFS. Therefore, this study aims to review the association between EV-LncRNAs and CFS, and to explore whether LncRNAs can be used as potential biomarkers for early identification and diagnosis of CFS, which put forward new ideas and a theoretical basis for the pathogenesis of CFS, as well as the identification of novel targeted therapies.